Is it possible to shift to hydrological boundaries?: the Ferghana Valley meshed system - Wegerich, Kai; Kazbekov, Jusipbek S.; Mukhamedova, Nozilakhon; Musayev, Sardorbek (2013)
The management of water resources according to hydrological boundaries at different implementation levels (river basin, irrigation system, or water user association) is promoted internationally. This approach to water management, especially for the basin, is starting to be challenged from different perspectives: representation within basins. appropriateness for basins in the south, and the challenges of merging boundaries for surface and groundwater sources. It has been challenged only recently in relation to its appropriateness for indigenously constructed (informal) irrigation systems. To these critiques, this paper adds the historical development and originally intended purpose of engineered irrigation systems and therefore calls into question whether it is always possible to introduce hydrological boundary management in the formal systems in Central Asia.